Apprenticeship Training in Germany? Investment or Productivity Driven? - Thomas Zwick (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2007)
The German dual apprenticeship system came under pressure in recent years because enterprises were not willing to offer a sufficient number of apprenticeship positions. A frequently made argument is that the gap could be closed if more firms would be willing to incur net costs during the training period. This paper investigates for the first time whether German enterprises on average indeed incur net costs during the apprenticeship period, i.e. if the impact of an increase in the share of apprentices on contemporary profits is negative. The paper uses the representative linked employer-employee panel data of the IAB (LIAB) and takes into account possible endogeneity of training intensity and unobserved heterogeneity in the profit estimation by employing panel system GMM methods. An increase in the share of apprentices has no effect on profits. This can be interpreted as a first indication that most establishments in Germany do not invest more in apprentices than their productivity effects during the apprenticeship period.
Keywords: 330